A fundamental study of the thermoelectrochemistry of ferricyanide/ferrocyanide: cation, concentration, ratio, and heterogeneous and homogeneous electrocatalysis effects in thermogalvanic cells. Issue 7 (29th May 2020) - Buckingham, Mark A.; Hammoud, Samer; Li, Huanxin; Beale, Conor J.; Sengel, Jason T.; Aldous, Leigh
Abstract : Thermocells can sustainably generate electricity from waste heat temperature gradients. This study investigates numerous fundamental aspects of thermocells, and how to explain and model such aspects. Abstract : Thermogalvanic cells typically utilise equimolar concentrations of the oxidised and reduced states of a redox couple in solution, sandwiched between two electrodes at dissimilar temperatures; entropy drives redox processes to occur at these electrodes, generating a potential difference and a current. However, significant gaps still exist in fundamental data and understanding of these 'thermocells'. In this study, thermocells based upon potassium ferricyanide, K3 [Fe(CN)6 ], and potassium ferrocyanide, K4 [Fe(CN)6 ], were investigated. The ratio of the oxidised and reduced states were systematically varied, and this had a significant effect upon the power produced; notably maximum power did not correspond to the equimolar ratio. A concentration study using equimolar ratios was also performed. Trends in the potential generated as a function of temperature (or 'Seebeck coefficient') were rationalised by the Nernst equation and Debye–Hückel theory. The trends in the current and the electrical power produced were successfully modelled using the Butler–Volmer equation. The effects of heterogeneous electrocatalysis were also explored (using platinum and two types of graphite) as well as homogeneous electrocatalysis, by the direct addition of alkali metal salts (as lithium, sodium, potassium, rubidium and caesium chlorides and sulphates). Clear trends were observed, and homogeneous and heterogeneous electrocatalysis had an additive effect when combined. Addition of CsCl was able to boost the maximum power output by upto ca. 80%, via both an increased Seebeck coefficient (through altered solvation) and through increased current ( via homogeneous electrocatalysis of electron transfer). Finally, a limited economic comparison was performed, which highlights how the use of non-stoichiometric ratios of the redox couple could improve the cost-per-power value of the systems.